2008
DOI: 10.1158/1541-7786.mcr-07-2005
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 9 Mediates CpG Oligonucleotide–Induced Cellular Invasion

Abstract: Toll-like receptor 9 (TLR9) belongs to the innate immune system and recognizes microbial and vertebrate DNA. We showed previously that treatment with the TLR9-agonistic ODN M362 (a CpG sequence containing oligonucleotide) induces matrix metalloproteinase-13 -mediated invasion in TLR9-expressing human cancer cell lines. Here, we further characterized the role of the TLR9 pathway in this process. We show that CpG oligonucleotides induce invasion in macrophages from wild-type C57/B6 and MyD88 knockout mice and in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 51 publications
(85 reference statements)
6
105
0
Order By: Relevance
“…The stepwise logistic regression revealed that TLR9 expression as well as advanced pathological stage was significantly correlated with the trend of breast cancer to metastasis. These data suggests that TLR9 may induce the invasion and metastasis of breast cancer as shown in some previouse in vitro studies, which may involve an up-regulation of matrix metalloproteinase-13 activity [10,13,14].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The stepwise logistic regression revealed that TLR9 expression as well as advanced pathological stage was significantly correlated with the trend of breast cancer to metastasis. These data suggests that TLR9 may induce the invasion and metastasis of breast cancer as shown in some previouse in vitro studies, which may involve an up-regulation of matrix metalloproteinase-13 activity [10,13,14].…”
Section: Discussionsupporting
confidence: 73%
“…Since TLR9 was recognized as the receptor for unmethylated CpG DNA of most bacteria and DNA viruses, many attention has been given to explore its anti-tumor effect. However, there were also some reports concerning the direct effect of TLR9 ligation on tumor behavior such as invasion and metastasis [5,10,[13][14][15]. Our study is the first to investigate the expression of TLR9 in large breast cancer specimens and correlate TLR9 with clinicopathological features of breast cancer.…”
Section: Discussionmentioning
confidence: 73%
“…For stable silencing TLR9 in T47D cells, the cells were transfected with TLR9-RNAi or Neo plasmid using Lipofectamine reagent, as described previously (16). Forty-eight hours after transfection, cells were subcloned onto 96-well plates using the limiting dilution method and single-cell clones were established.…”
Section: Methodsmentioning
confidence: 99%
“…In cancer, tumor cells death results in release of numerous proteic or nucleic DAMPs that activate TLRs of both immune/stromal cells and epithelial cancer cells. Increasing evidence has indicated that TLRs expression by cancer cells and immune cells seems to be twofold by either promoting or inhibiting tumor progression [6,15,16].…”
Section: Introductionmentioning
confidence: 99%